The Use of an Augmented Reality Application to improve User Experience in Museums in São Luís - Maranhão - Berthier, Gabriel Nogueira; Gomes Jr., Daniel Lima; Maia, Ivana Márcia Oliveira; Paiva, Anselmo Cardoso de (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2021)
Museums are often acknowledged as a place to get involved into education, history and the world of art, serving large communities with the access to their exhibits as well as being seen as a knowledge source provided by their guides, collections, archives and others. Whilst visitors' experience in such given contexts may have been almost the same for a long time in which the interaction with the displayed artifacts and the experience within the context is restrained due to impositions to prevent visitors from handle assets and collections -, in many museums, gradually, the approach towards their visitors has changed as an attempt to improve the quality of experience offered. One strategy applied to improve visitors' experience in an exhibition environment is to use Augmented Reality (AR) as a manner to bring the user into a more active role and witness exhibitions at their own pace. This strategy consists in the employment of Augmented Reality in order to supply the visitor with a more detailed and interactive perspective of the assets presented, extending the comprehension of the surrounding space and adding an extra informative and interactive real time layer. This project's main goal is to provide an augmented reality application to be used by São Luís museums' visitors, in order to make exhibitions more attractive and educative to a large percentage of the population, as long as they have access to smartphones and mobile devices. The developed application was done focusing on fast development and recognition quality. Also, experiments using 2D and 3D shapes were conducted in order to prepare the system for future realistic fiducial markers and real life objects. The results satisfied the usage concepts, although latency and performance are still a concern when regarding multi-targets and connecting to a remote web service. The construction of an AR system has enough support to deliver both tracking and display virtual objects with no major performance loss, hence identifying one target at time and generating virtual content during usage can be done in a scenario such as the museum metaphor, accomplishing the conceptual goals aimed prior to the developed app.